Inequalities in life expectancy by educational level and its decomposition in Barcelona, 2004-2018 - Xavier Bartoll-Roca; Maica Rodríguez-Sanz; Esther Sánchez-Ledesma; Katherine Pérez; Carme Borrell (Elsevier, 2022)
Objective: To analyse the gap in life expectancy by educational level in the city of Barcelona from 2004 to 2018 and to decompose this gap by age and causes of death. Method: We computed abridged life tables at the age of 25 years by sex from 2004 to 2018 using standard methods. Educational level was categorised in two groups (lower secondary or less vs. upper secondary or higher education). The life expectancy gap was further decomposed by age and by causes of death based in Arriaga's method in 5-year age blocks up to the age of ≥ 90 years and broad causes of death using ICD-10 codes. Results: The life expectancy gap at 25 years by educational level oscillated without trend at around 3.08 years for men and 1.93 years for women. Decomposition by age showed a favourable significant shift in the contribution to this gap from young to older ages for men, with few changes for women. Decomposition by causes of death showed that the diseases concentrating the largest share of the contribution were neoplasms and respiratory and circulatory disease. There was a significant downward trend in external causes for men and in infectious diseases for both men and women but a significant upward trend for respiratory disease for both sexes. Conclusions: The stability of the life expectancy gap by educational level during the period analysed resulted from a combination of divergent trends by age and causes of death among high and low educational levels. Resumen: Objetivo: Analizar la brecha en la esperanza de vida por nivel educativo en la ciudad de Barcelona desde 2004 hasta 2018, y descomponer esta brecha por edad y causas de muerte. Método: Se calcularon tablas de vida abreviadas a la edad de 25 años por sexo desde 2004 hasta 2018 utilizando métodos estándar. El nivel educativo se clasificó en dos grupos: secundaria inferior o menor frente a secundaria superior o educación superior. La brecha de la esperanza de vida se descompuso además por edad y por causas de muerte según el método de Arriaga en bloques de edad de 5 años hasta la edad de ≥90 años y causas amplias de muerte utilizando los códigos de la CIE-10. Resultados: La brecha de la esperanza de vida a los 25 años por nivel educativo osciló sin tendencia en torno a los 3,08 años para los hombres y 1,93 años para las mujeres. La descomposición por edad mostró un cambio favorable a esta brecha desde las edades jóvenes a las mayores en los hombres, con pocos cambios en las mujeres. La descomposición por causas de muerte mostró una mayor contribución de las neoplasias y las enfermedades respiratorias y circulatorias. Hubo una tendencia a la baja en las causas externas en los hombres, y en las enfermedades infecciosas tanto en los hombres como en las mujeres, pero al alza en las enfermedades respiratorias para ambos sexos. Conclusiones: La estabilidad de la brecha de la esperanza de vida por nivel educativo durante el periodo analizado fue el resultado de una combinación de tendencias divergentes por edad y causas de muerte entre los niveles educativos altos y bajos.